Factors associated with depression, anxiety, and satisfaction with life among Malaysian parental caregivers of adolescent psychiatric patients: a cross-sectional study - Cham, Choy Qing; Ibrahim, Norhayati; Kalaman, Clarisse Roswini; Ho, Meng Chuan; Visvalingam, Uma; Ahmad Shahabuddin, Farah; Abd Rahman, Fairuz Nazri; Halim, Mohd Radzi Tarmizi A.; Harbajan Singh, Manveen Kaur; Azhar, Fatin Liyana; Yahya, Amira Najiha; Roslan, Samsilah; et al. (Cambridge University Press, 2024)
Depression and anxiety are prevalent mental health issues worldwide, especially among parental caregivers. By expanding the family stress model, this cross-sectional study investigated the relevant factors associated with depressive symptoms, anxiety symptoms, and satisfaction with life among Malaysian parental caregivers of adolescent psychiatric patients. Data were collected through questionnaires (N = 207) across five major public hospitals through convenience sampling. Participants answered questionnaires measuring financial strain, caregiver burden, relationship quality, belief in mental illness, perceived COVID-19 stress, satisfaction with health services, depressive symptoms, anxiety symptoms and life satisfaction. Findings revealed that relationship quality among spouses, COVID-19 stress and caregiver burden were significantly correlated with anxiety symptoms, depressive symptoms and satisfaction with life. The multiple regression model also suggested that depressive symptoms (β =.613, p <.001), anxiety symptoms (β=.657, p <.001) and relationship quality among spouses (β =.264, p <.001) were the most influential predictors of anxiety symptoms, depressive symptoms and satisfaction with life respectively. By addressing the mental health needs of parental caregivers, this study can contribute to improving the overall quality of care and support provided to adolescent patients and their caregivers in Malaysia and beyond.